Analysis Of Differences In Student Learning Outcomes In Educational Research Courses Using The Arias Learning Model (Assurance, Relevance, Interest, Assesment, Satisfaction ) - Setyawan, Trinovandhi; Kusmawati, Wiwik; Budijanto, Budijanto; Ernata, Yusvidha; Irawan, Dedy; Nuh, Fuad Azhar (JUPE : Jurnal Pendidikan Mandala, 2025)
The aim of this research is to determine differences in student learning outcomes in Educational Research courses using the ARIAS learning model. The research method is a quasi-experimental method. The sampling technique was simple random sampling. The sample is students from Class 2021 class F as the experimental class and students from Class 2021 class G as the control class. The data collection technique uses tests and non-tests. The instruments are objective tests of the multiple choice type and non-test instruments in the form of questionnaires. The data obtained were analyzed using the prerequisite normality test and homogeneity test. The results of the t-test carried out using the SPSS program showed that the tcount value was greater than the ttable value, meaning that there was a significant difference in the learning outcomes of students in the experimental class and the control class, so it could be concluded that there was a difference in student learning outcomes in the Educational Research course. using the ARIAS learning model.